2015
DOI: 10.1021/acs.chemmater.5b01248
|View full text |Cite
|
Sign up to set email alerts
|

High Stability of Immobilized Polyoxometalates on TiO2 Nanoparticles and Nanoporous Films for Robust, Light-Induced Water Oxidation

Abstract: Solutions to two general limitations in the immobilization of molecular water oxidation catalysts (WOCs) on nanoparticle or photoelectrode surfaces have been investigated: (a) a straightforward electrostatic method to bind charged WOCs more effectively to these surfaces and (b) a method to increase the concentration of the semiconductor- and/or electrode-immobilized WOCs so they can be spectroscopically characterized in this form. Polyoxometalate (POM) WOCs, known to be fast, selective, and oxidatively stable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(40 citation statements)
references
References 52 publications
0
40
0
Order By: Relevance
“…On the other hand, understanding the mechanism of water splitting, detecting active species and correlating the activity with structure have been followed by different groups. [107a,b] Synthesis of new materials involved use of metal salts, metal organic frameworks, and polyoxometalates as the precursor. MOF derived nano and microstructure have been recently explored for the water splitting .…”
Section: Electrochemical Energy Conversionmentioning
confidence: 99%
“…On the other hand, understanding the mechanism of water splitting, detecting active species and correlating the activity with structure have been followed by different groups. [107a,b] Synthesis of new materials involved use of metal salts, metal organic frameworks, and polyoxometalates as the precursor. MOF derived nano and microstructure have been recently explored for the water splitting .…”
Section: Electrochemical Energy Conversionmentioning
confidence: 99%
“…The fabrication of dye‐sensitized PEC cells by stable co‐immobilization of molecular photosensitizers and electrocatalysts with APTES chemistry using TiO 2 and indium tin oxide was reported (Figure g) . In addition to organometallic electrocatalysts, Hill's group reported that negatively charged tetranuclear polyoxometalate (POM) OER catalysts can be electrostatically adsorbed on TiO 2 or Fe 2 O 3 photoanodes after modification with APTES. However, their works have limitations regarding the low stability of immobilized POM catalysts without protective layer by atomic layer deposition to prevent the detachment of POM electrocatalysts .…”
Section: Immobilization Of Molecular Electrocatalysts By Covalent mentioning
confidence: 99%
“…Rather than modification of molecular electrocatalysts, photoelectrode surfaces can also be covalently modified with functional groups to avoid altering the activity of molecular electrocatalysts, to immobilize molecular electrocatalysts difficult to covalently modify, or to form more stable chemical bonding , . In particular, alkoxysilanes with a specific end‐functional group have been widely used for surface modification of various photoelectrodes and electrodes, such as TiO 2 ,, , ZnO,, SnO 2 ,, and Si, due to their well‐known and simple chemistry. When using 3‐aminoproyltriethoxysilane (APTES) in particular, amine groups can be readily displayed on photoelectrode surfaces by its hydrolytic condensation and used to immobilize molecular electrocatalysts covalently and electrostatically.…”
Section: Immobilization Of Molecular Electrocatalysts By Covalent mentioning
confidence: 99%
“…Several studies have focused on direct binding of the POM to photoactive metal oxides, such as TiO 2 and hematite. Recently, our group published a report in which we treated TiO 2 with 3-aminopropyltrimethoxysilane (APS) to generate a cationic surface that strongly bound the highly negatively charged POM WOC, Ru 4 Si 2 (Lauinger et al, 2015 ). This was effective for surface immobilization of the POM and light driven water oxidation.…”
Section: Heterogeneous Polyoxometalate Water Oxidation Catalysts (Wocmentioning
confidence: 99%